A dependência entre os setores da indústria e de serviços no Brasil para os anos de 2003 e 2013 - Hegele, Fabiane (2018)
For a long time, the service sector was neglected by economic literature, even it was considered unproductive. However, with the technological innovations, the services acquire new functions. The increase of the services share occurs in the beginning of the information revolution in 1970. In this context occurs the passage from the Mass Production Paradigm to the Flexible Networks Paradigm. From the mid-twentieth century, the services share in terms of GDP and employment increases in advanced economies. This phenomenon is also perceived by Brazilian economy. In addition, the service sector has an important role in supplying inputs to industrial sector. In 2011, more than 30% of added value in Brazilian exported manufactures corresponds to domestic services and, in total exports, the share exceeds 40%. This dissertation aims to investigate whether the dependence between industry and services in Brazil increased between 2003 and 2013. Input-Output Analysis is the methodology used, it is based on matrices estimated by the Centro de Economia Regional e Urbana da Universidade de São Paulo (NEREUS), the matrix of 2003 is disaggregated in 56 activities and the other in 68. Three applications are used to the input-output matrices. The first one, Dependency Ratio, it is used to measure the degree of dependence in the relationship between groups of industry segments and services. As a result, the industry's dependence on services increased between 2003 and 2013, specifically in relation to Distribution Services and Producer Services. With the second application, Hypothetical Extraction, it is intended to identify the service segments that most impact the GDP of the Brazilian industry, in relative terms of the three sectors of the economy (farming, industry and services). The most important segments as buyer and seller of products on the market were Commerce and Transportation, Warehousing and Mail. The last application, Network Analysis, it is used to compare the location of the service groups and the other economy activities. It was noticed that, in 2003 and 2013, the segments Trade, Transportation, Warehousing and Post and Financial Intermediation and Insurance located at the center of the network, it indicates the importance of these segments to the economy. With the increasing dependence between industry and services in Brazil between 2003 and 2013, it is understood that more attention should be given to the services sector, including its participation in industrial policy discussions.